Comparative Analysis Of Bumi Serpong Damai City (Bsd) And Nusantara Capital City (Ikn) In The Conceptual Framework Of Sustainable Cities - Sakkar Risdollah, Aris; Mustafa, Mursyid; Mega Januarti putri, Andi (International Journal of Science, Technology & Management, 2025)
BSD and IKN City are new cities built in Indonesia with the concept of Sustainable Cities. This research will examine the concepts of BSD and IKN City and the physical development that has been carried out regarding their similarities and differences in the conceptual framework of a coherent city. Using descriptive analysis with purposive sampling. The results of the study found that the basic idea of sustainable cities is basically implemented in the concept and development of BSD and IKN City, especially in its attention to the environment and the application of smart technology in facilitating city management and social life of urban communities.